Eucalypt forests dominated by epicormic resprouters are resilient to repeated canopy fires. (5th July 2019) - Collins, Luke
Abstract: Wildfire occurrence and severity are projected to increase in response to anthropogenic climate change, leading to fire regimes that may exceed the limits of tolerance for some species. Plants capable of regenerating from aerial shoots following high intensity fires, termed 'epicormic resprouters', are assumed to be resilient to changes in fire regimes. However, empirical tests of the response of epicormic resprouters to extreme fire regimes, such as repeated canopy fires at short intervals, are currently lacking. This study examined the effect of combinations of understorey fire and canopy fire across two successive wildfires (2007, 2013) on the resilience of eucalypts that resprout epicormically. The study took place in a temperate eucalypt forest in south eastern Australia. Measures used to infer community resilience included stem topkill and damage, and seedling recruitment. It was predicted that: (a) stems will exhibit lower resistance (i.e. increased topkill and damage) to canopy fire than understorey fire; (b) recruitment will be higher following canopy fire than understorey fire; (c) prior exposure to canopy fire will reduce stem resistance and recruitment in response to subsequent wildfires; and (d) stem resistance will vary depending on bark traits. Topkill of saplings and small stems (<30 cm diameter at breast height) was higher in sites that recently (i.e. 2013) experienced canopy fire as opposed to understorey fire. Recent fire severity had no effect on topkill of large trees. Tree species with dense bark on the main stem and larger branches were less prone to topkill or partial stem and branch mortality than species with fibrous bark or exposed branches. Seedling recruitment was greater following canopy fire than understorey fire. Exposure to past canopy fire (i.e. in 2007) did not decrease stem resistance or recruitment. Synthesis. The results of this study suggest that communities of eucalypts that can resprout epicormically following fire will experience demographic shifts following repeated canopy fires. However, given the high resistance of large trees and rapid post‐fire recovery of the seedbank, ecosystem conversion appears unlikely. The findings support the presumption that forest communities of epicormic resprouters are highly resilient to shifts in fire regimes. Abstract : Communities of eucalypts that can resprout epicormically show resilience to biome change following repeated canopy fires, owing to the resistance of large trees and rapid post‐fire recovery of the seedbank. However, repeated canopy fires will change forest structure by increasing stem and branch mortality, leading to reduced stocking of small trees and lowering of the canopy.